Psicodiagnóstico interventivo: novos rumos na prática e na pesquisa em psicologia clínica - Schaurich, Aline Praetzel (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation aimed to deepen the studies on Intervention Psychodiagnosis of psychoanalytic orientation as an effective intervention clinical practice that meets the current changes and needs. In Section I, we present a theoretical article on psychodiagnosis by covering definitions, historical and philosophical foundations and the process of evolution of clinical practices until reaching the purpose of Intervention Psychodiagnosis. It is based on studies systematized by researchers (Barbieri, 2004, 2008, 2009, 2010; Paulo, 2006; Tardivo 2007). This practice has been the focus of studies for meeting the current needs and also for being widely based on the epistemological presuppositions of qualitative research. Thus, it represents to professionals who use it not only an effective resource in assessing/intervening, but also the possibility of integrating knowledge generated through clinical practice with the production of scientific knowledge. In the empirical article of Section II we present the study of clinical case of one adolescent who was assisted according to Intervention Psychodiagnosis. This technique accomplished the two objectives set: as an assessment/intervention technique and as a method of scientific investigation based on the presuppositions of qualitative research. This study then aimed to deepen the theoretical knowledge of the technique as well as to contribute to consolidate this scientific method in researches in Clinical Psychology.
Keywords: Psicodiagnóstico interventivo de orientação psicanalítica; Psicologia clínica; Pesquisa qualitativa; Psychodiagnosis and therapeutic assessment; Clinical psychology; Qualitative research; ACCNPQ::Ciências Humanas::Psicologia